Lorentz Connections and Gravitation - Pereira, J. G. (American Institute of Physics (AIP), 2012)
The different roles played by Lorentz connections in general relativity and in teleparallel gravity are reviewed. Some of the consequences of this difference are discussed.
Keywords: Lorentz connections; general relativity; teleparallel gravity